SYNTHESIS OF SCHIFF BASE VERDANTIOL BY SIMPLE CONDENSATION - Niken Oktaviani; Leny Heliawati; Yudhie Suchyadi (Journal of Science Innovare, 2019)
Schiff base is a chemical compound that is formed from the reaction between aldehydes and primary amines by condensation and produces by-products in the form of water. Schiff base is the raw material that is added in making Fragrance. The purpose of this study was to determine the method of synthesis of Schiff base verdantiol with simple condensation. The research method was carried out with four stages: preparation, synthesis, testing and measurement of parameters, and calculations. Preparation includes weighing the raw material Schiff base verdantiol. Schiff base synthesis is carried out by stirring at a temperature of about 90°C ± 5° C (Arctender, 1969) with a modification time of 15 minutes, 30 minutes, 1 hour, 2 hours and 3 hours. Testing and measurement parameters include organoleptic, density and specific gravity tests in pycnometer and compound confirmation using Gas Chromatography Mass Spectrometry. The results showed that the optimum synthesis of Schiff base verdantiol compounds was carried out at a heating time of 2 hours. The results of odor, color, density and gravity specifications heating time 2 hours according to specifications with the standard. GCMS confirmation results at 2 hours percent similarity are above 94%.